A Review of FOXI3 Regulation of Development and Possible Roles in Cancer Progression and Metastasis - Mukherjee, Angana; Hollern, Daniel P.; Williams, Oluwasina G.; Rayburn, Tyeler S.; Byrd, William A.; Yates, Clayton; Jones, Jacqueline D. (Frontiers in Cell and Developmental Biology, 2018)
Development and cancer share a variety of functional traits such as EMT, cell migration, angiogenesis, and tissue remodeling. In addition, many cellular signaling pathways are noted to coordinate developmental processes and facilitate aspects of tumor progression. The Forkhead box superfamily of transcription factors consists of a highly conserved DNA binding domain, which binds to specific DNA sequences and play significant roles during adult tissue homoeostasis and embryogenesis including development, differentiation, metabolism, proliferation, apoptosis, migration, and invasion. Interestingly, various studies have implicated the role of key Fox family members such as FOXP, FOXO, and FOXA during cancer initiation and metastases. FOXI3, a member of the Forkhead family affects embryogenesis, development, and bone remodeling; however, no studies have reported a role in cancer. In this review, we summarize the role of FOXI3 in embryogenesis and bone development and discuss its potential involvement in cancer progression with a focus on the bone metastasis. Moreover, we hypothesize possible mechanisms underlying the role of FOXI3 in the development of solid tumor bone metastasis.